Hepatitis A virus structural protein pX interacts with ALIX and promotes the secretion of virions and foreign proteins through exosome-like vesicles. Issue 1 (1st January 2020) - Jiang, Wang; Ma, Pengjuan; Deng, Libin; Liu, Zhi; Wang, Xu; Liu, Xiyu; Long, Gang
ABSTRACT: Hepatitis A virus (HAV), a classic nonenveloped virus, has recently been found to be released mainly in the form of quasi-enveloped HAV (eHAV) by hijacking host endosomal sorting complexes required for transport (ESCRT) complexes. Unlike the nonenveloped virion, eHAV contains the viral protein pX on the surface of the HAV capsid as an extension of VP1. How HAV capsids acquire the host envelope and whether the pX protein is involved in this process were previously unknown. Here, we analyse the role of pX in foreign protein secretion in exosome-like extracellular vesicles (EVs) and the formation of eHAV. Fusion of pX to eGFP guided eGFP into exosome-like EVs through directing eGFP into multivesicular bodies (MVBs), and apoptosis-linked gene 2-interacting protein X (ALIX) release was significantly enhanced. Coimmunoprecipitation (co-IP) demonstrated the interaction between pX and the ALIX V domain. Removal of the C-terminal half of pX abolished eHAV release and reduced the interaction between the HAV virion and ALIX. Finally, the C-terminal half of pX alone was sufficient for loading eGFP into EVs by interacting with ALIX. In conclusion, the C-terminal part of pX is important for eHAV production and may have potential for large protein complex loading into exosome-like EVs for therapeutic purposes.